1986
DOI: 10.1038/clpt.1986.195
|View full text |Cite
|
Sign up to set email alerts
|

Metoprolol and debrisoquin metabolism in nigerians: Lack of evidence for polymorphic oxidation

Abstract: The role of genetic polymorphism in the oxidative metabolism of metoprolol and debrisoquin was investigated in a population of 138 unrelated Nigerians. The debrisoquin/4-hydroxydebrisoquin 0-8 hour urinary ratio (D/HD) correlated significantly with the metoprolol/alpha-hydroxymetoprolol 0-8 hour urinary ratio (M/HM) (rs = 0.54; P less than 0.001), the metoprolol/H117-04 [4-(2-hydroxy-3-isopropylaminopropoxy)-phenylacetic acid] 0-8 hour urinary ratio (M/H117-04) (rs = 0.42; P less than 0.001), and the plasma me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
1

Year Published

1988
1988
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 0 publications
0
29
1
Order By: Relevance
“…The results indicate that Koreans, like Japanese and Chinese, have a very low frequency of the PM phenotype of metoprolol oxidation compared with white British subjects (Iyun et al, 1986;McGourty et al, 1985).…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The results indicate that Koreans, like Japanese and Chinese, have a very low frequency of the PM phenotype of metoprolol oxidation compared with white British subjects (Iyun et al, 1986;McGourty et al, 1985).…”
Section: Discussionmentioning
confidence: 85%
“…We have recently reported that Japanese and mainland Chinese have a relatively low frequency of the PM phenotype for metoprolol oxidation (Horai et al, 1989) compared with a white British population (Iyun et al, 1986;McGourty et al, 1985), and that the metabolic capacity differs between the extensive metabolisers (EMs) of the two Oriental populations (Horai et al, 1989 . Statistical significance was defined as P < 0.05.…”
Section: Introduction Methodsmentioning
confidence: 99%
“…Similarly, Carr et al (1978) phenotype three out of their 50 subjects and Clark (1985) found two subjects in over 100 individuals whose metabolic ratio would not allow accurate phenotyping. Clark (1985) (Ishizaki et al, 1987) and others (Iyun et al, 1986). Mass screening tests to define acetylator status in a selected population become more feasible and convenient if an adequate noninvasive procedure can be developed.…”
Section: Discussionmentioning
confidence: 99%
“…Reports on the prevalence of PMs in African populations differ widely, with estimates varying in the range of 0%-19% [21,[35][36][37][38]. There is also a wide range in the incidence of PMs reported in African-Americans, 1.9%-7.3% [39][40][41][42].…”
Section: Pm Phenotypementioning
confidence: 99%